ACTIVATED CARBONS OBTAINED BY PYROLYZING OF RESORCINOL FORMALDEHYDE GELS - M. R. Vasic; R. Petrović (Journal of Engineering & Processing Management, 2010)
Activated carbon is used in different industrial domains due to highly developed specific surface area and its specific chemistry. Properties of activated carbons obtained by pyrolyzing formaldehyde gels are presented in this paper. The gels were synthesized on several temperatures in order to follow the kinetics of gelling process. The relationship between gel synthesis conditions and properties of activated carbons was examined especially in terms of its influence on value of specific surface area and porosity. Carbon was activated with water vapor and cited activation was examined in terms of influence of water vapor on the value of specific surface area and porosity. The capability of modifying activated carbon surface by HN03 oxidation was examined. Characterization of activated carbons was carried out using methods of BET and SEM, IR spectroscopy and by determination of surface electric density.
Keywords: Activated carbons; gels; kinetics